IL-12 concentrations in the aqueous humor and serum of diabetic retinopathy patients - Gverović Antunica, Antonela (Array, 2012)
Background Previous studies suggest that inflammation plays an important part in the pathogenesis of diabetes. Cytokines may have a role in both positive and negative control of immunological reactions. Among many cytokines, interleukin 12 (IL-12) is known to be a strong pro-inflammatory cytokine. Methods A total of 76 participants were enrolled in this study and classified into four groups: 23 diabetic patients with non-treated retinopathy, 17 diabetic patients with treated retinopathy, 12 diabetic patients without retinopathy, and 24 healthy control patients. Serum and aqueous humor samples were taken for the analysis of IL-12 concentration. Results The aqueous humor IL-12 concentration was significantly elevated in the patients with non-treated diabetic retinopathy (χ2(3, n  = 76) = 27.137 ; p < 0.001). No significant differences in IL-12 serum concentrations between the groups were found (F =  0.405, p = 0.750). Correlation analysis of IL-12 concentrations in the serum and aqueous humor showed a linear association between the two variables only in non-diabetic patients (p  = 0.003). Conclusions This is the first study to show a significantly higher concentration of pro-inflammatory cytokine IL-12 in the aqueous humor of non-treated diabetic retinopathy patients in comparison with diabetic patients treated for retinopathy, without retinopathy, or with healthy individuals. Because the serum levels of IL-12 did not differ considerably between the studied groups, it is plausible that this is due to its local production and secretion.